Developing Speaking Course Book for English Department Students - Kartini, Sri; Lestari, Lies Amin; Munir, Ahmad (Fakultas Ilmu Budaya, Universitas Mulawarman, 2019)
The study aims at describing the development process, the quality, and the practicality of Speaking Course Book entitled Speaking for Daily Activities for English Department students of the private university in West Surabaya. It employs Design and Development Research (DDR) and uses Richey and Klein’s model of DDR collaborated with Richard’s model of material development. The development processes of the book support Richey and Klein’s model of DDR, Richards’ model of development material and material development for speaking skills proposed by Bao. The mean score of items in evaluation checklist is 3.80 meaning that the quality of the book is very good, and it fully matches the characteristics of a good speaking course book. The appraisal forms show that both the lecturer and the students could use the book very easily. Also, the mean score of items in observation checklist is 3.65 meaning the practicality of the book is very good. Penelitian ini bertujuan untuk mendeskripsikan proses pengembangan, kualitas, dan kepraktisan Speaking Course Book untuk mahasiswa Jurusan Bahasa Inggris sebuah universitas swasta di Surabaya Barat, yaitu Speaking for Daily Activities. Penelitian ini merupakan Penelitian Pengembangan yang menggunakan kolaborasi antara model Richey and Klein dalam Penelitian Pengembangan dan model pengembangan materi dari Richard. Proses pengembangan buku ajar mendukung model Penelitian Pengembangan dari Richey and Klein, model pengembangan materi dari Richards, dan pengembangan materi untuk keterampilan berbicara oleh Bao. Skor rata-rata item dalam daftar evaluasi adalah 3,80, yang berarti kualitas buku sangat bagus dan sangat sesuai dengan karakteristik buku ajar berbicara yang baik. Kepraktisan buku sangat baik. Hal ini bisa dilihat dari form isian yang menunjukkan bahwa dosen dan mahasiswa dapat menggunakan buku tersebut dengan sangat mudah. Selain itu, skor rata-rata item dalam daftar pengamatan adalah 3,65 yang berarti sangat bagus.